A Profile Matching-Based Decision Support Framework for Selecting Generative AI Tools in Higher Education - Pratistha, Indra; Anggaswara, Aditha Diva; Saputra, Gusti Bagus Arya; Krisna, I Gede Anugrah Adi; Sudipa, I Gede Iwan (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2026)
This study aims to develop a decision-making model for determining the best AI application, specifically for students, in selecting the best alternative based on various criteria. This study used the Profile Matching Method to rank alternatives. Data was collected from students through an online survey, with criteria including ease of use (C1), task completion support (C2), creativity and idea support (C3), output quality and accuracy (C4), flexibility of use (C5), and access cost (C6). A decision-making analysis was conducted to determine the application that best suited students' preferences and identified the factors that most influenced their choice. The results showed the ChatGPT application alternative (A1) as the best student choice.